To Study the Bacteriological Profile and Antimicrobial Susceptibility Patterns of Pathogens Isolated from Urine Samples in Icu Patients at a Tertiary Care Hospital in North India - Srivastava, Anshika; Chauhan, Geetanshu; Afaq, Nashra (Journal of Neonatal Surgery, 2025)
Background: Intensive care units (ICUs) are hotspots for multidrug-resistant (MDR) bacterial infections, which significantly contribute to patient morbidity and mortality. Prompt identification of pathogens and knowledge of their resistance profiles is essential for empirical therapy and infection control. Aim and Objective: To evaluate the distribution of pathogens from various clinical specimens in ICU patients and to analyze their antibiotic susceptibility patterns. Material and Methods: A retrospective study was conducted in the Department of Microbiology, Sharda Hospital, Greater Noida, over a defined period. A total of 2,125 clinical samples from ICU patients were processed according to standard microbiological protocols. Identification of isolates was done by biochemical testing, and antimicrobial susceptibility was determined by the Kirby-Bauer disk diffusion method as per CLSI guidelines (2023) [1]. Results: In the present study out of the 2,125 samples, blood constituted 46%, urine 30%, respiratory 20%, and pus 4%. A total of 285 pathogens were isolated, with respiratory samples showing the highest positivity (46%). The most common organisms were E. coli (24%), Acinetobacter spp. (23%), Klebsiella spp. (13%), and Staphylococcus aureus (10%). Among Enterobacteriaceae, carbapenems (43%), tigecycline (43%), and aminoglycosides (41–42%) were the most effective drugs. Acinetobacter spp. showed high sensitivity to minocycline (68%) and tigecycline (45%) but complete resistance to nitrofurantoin and norfloxacin. Pseudomonas aeruginosa responded well to amikacin (79%) and carbapenems (75%). Gram-positive isolates like S. aureus and Enterococcus spp. were highly susceptible to linezolid (95–100%) and vancomycin (50–78%). Conclusion: The findings highlight a high burden of multidrug-resistant pathogens in ICU settings, with varying resistance patterns requiring continuous surveillance and rational antimicrobial stewardship